Instructional Learning Model on WhatsApp Media Problem in a Pandemic Covid 19 Period - Mohammad Imam Sufiyanto; Rocyhan Yasin; Hesty Kusumawati (Pedagogik Journal of Islamic Elementary School, 2021)
The aim of this study is to examine the impact of Problem-Based Instruction (PBI) on elementary school students in the Pamekasan area. This research adopts a descriptive qualitative approach, with 150 elementary school students (78 boys and 72 girls) as participants. Data collection techniques include interviews and questionnaires, while counseling serves as the research instrument. Data analysis utilizes sampling methods. The study reveals that among the 150 students distributed across three classes, each with 50 members in a WhatsApp group, the interpretation scale ranges from 307 to 400, indicating a very good performance during the COVID-19 pandemic online via the WhatsApp platform. The findings suggest that the PBI learning model, when conducted through social media platforms like WhatsApp, is highly suitable for elementary education, providing effective learning experiences for students.